Manfaat Kegiatan Sosial Grup PS Store: Social Entrepreneurship atau Corporate Social Responsibility - Mufidah Said (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2023)
Purpose PS Store is to carry out many social activities. This study examines whether social activities are included in acts of generosity, corporate social responsibility or social entrepreneurship. Furthermore, it emphasizes the perceived benefits for society, consumers and employees. Methodology The number of respondents was taken by convenience sampling method of 30 people. The technique used with triangulation. Findings Respondents' answers 70% of respondents were very happy with the existence of the PS Store business 15% of respondents were happy with the existence of the PS Store business 10% were normal with the existence of the PS Store business 5% of respondents were not happy with the existence of the PS Store business. Ps Store's social actions cannot yet be included in the Social Entrepreneurship category, which tends to be more generous or philanthropic and also corporate social responsibility. Suggestion Further research examines social actions with benefits for companies, consumers, and employees.